ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DAN HARGA POKOK PENJUALAN TERHADAP LABA BERSIH : STUDY KASUS MIE AYAM KEMBAR KECAMATAN NAMORAMBE KABUPATEN DELISERDANG - Khairatun Nazah (LP2M Universitas Bina Bangsa, 2024)
By calculating the correct cost of production, the owner can determine the right selling price so that he can optimize the desired profit. The purpose of this study is to recognize and determine how to calculate the appropriate cost of production and cost of goods sold to be applied to Twin Chicken Noodles. Data analysis was carried out using a descriptive method. The calculation of the selling price produced by Full Costing is Rp. 12,947, there is a price difference of Rp. 947 with the selling price of MSMEs. The calculation of the selling price obtained by variable cost is Rp. 12,892, the difference between the variable cost and the selling price of MSMEs is Rp. 892. The selling price calculated with full cost and variable cost is higher than the selling price of MSMEs. The conclusion of this study is that the calculation of the production HPP carried out by MSMEs, has not reflected the actual situation, so that the cost budget that has been made and the selling price set by MSMEs have not reflected the profit desired by the owner of 50%.